A self-lubricating phenolic resin-based composite material and a preparation method thereof
Patent Information
- Application Number
- CN202311504629.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-13
AI Technical Summary
1、本发明通过添加充当应力集中点的凹凸棒石或其衍生物和增强纤维的配方优化,吸收施加的外部能量的同时阻止材料内部银纹产生及生成,增加了树脂抗弯曲和压缩强度,改善了酚醛树脂基体的塑性形变区间,提高了材料韧性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid lubricating materials technology, and in particular to a self-lubricating phenolic resin-based composite material and its preparation method. Background Technology
[0002] With the continuous development of industrial equipment and transportation facilities, more and more moving mechanisms are operating under increasingly varied and demanding conditions. Due to the increasing size of moving mechanisms and the special nature of their working environments, higher requirements are placed on the load-bearing capacity, reliability, and service life of their materials. The design and development of materials with excellent self-lubricating properties, wear resistance, reliability, and suitability for multiple working conditions has gradually become a research hotspot in various countries. Polymer composite materials, due to their advantages such as light weight, high chemical stability, and strong designability, are widely used in various fields such as automobiles, wind power, and the military.
[0003] Phenolic resin (PF) is a thermosetting polymer material formed by cross-linking and curing phenols and aldehydes under the catalysis of acid or alkali. This resin possesses high mechanical strength and good heat resistance, and can be blended with other polymers to optimize performance. As one of the three major thermosetting resins, it is widely used in transportation, construction, aerospace, and other fields. Furthermore, compared to specialty plastics such as cyanate ester resins and polyimide (PI), it has the advantage of low cost. However, pure PF products are brittle, have poor toughness, insufficient rigidity and strength, and inherently poor wear resistance, limiting their application in high-end equipment lubrication materials.
[0004] It is well known that adding reinforcing fillers to polymer matrices is an effective method to improve the mechanical and tribological properties of materials. However, moving mechanisms face complex and variable operating conditions, and the added single reinforcing filler needs to meet its tribological performance requirements under multiple conditions of dry friction and oil lubrication. Oil lubrication reduces the flash temperature in the friction contact area, inhibits material transfer, and ultimately affects the formation of the friction film, thus impacting tribological properties. Simultaneously, dry friction generates high flash temperatures in the friction contact area, accelerating the deformation and transfer of polymer materials, and increasing the risk of material wear and loss.
[0005] Currently, no research reports indicate that phenolic composite materials can be applied to harsh and complex working conditions. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a high-strength, wear-resistant, self-lubricating phenolic resin-based composite material that is suitable for both dry friction and oil lubrication conditions.
[0007] Another technical problem to be solved by the present invention is to provide a method for preparing the self-lubricating phenolic resin-based composite material.
[0008] To solve the above problems, the present invention provides a self-lubricating phenolic resin-based composite material, characterized in that the composite material is composed of the following components in mass fractions: 55%~85% phenolic resin, 5%~25% nano-functional filler, and 10%~20% reinforcing fiber.
[0009] The phenolic resin is a thermosetting phenolic resin powder.
[0010] The nano-functional filler is any one of attapulgite powder or its derivatives, with a particle size of 10 nm to 100 nm.
[0011] The nanofunctional filler is attapulgite with a purity greater than 98% and is dissociated.
[0012] The reinforcing fiber is any one or more mixed fibers selected from carbon fiber, aramid fiber, glass fiber, and titanate whisker fiber, with an aspect ratio greater than 20.
[0013] The preparation method of the self-lubricating phenolic resin-based composite material as described above includes the following steps: (1) Weigh according to the proportions; (2) Dry the nano-functional filler and reinforcing fiber at 60℃~120℃ for 1~24h to obtain the dried nano-functional filler and reinforcing fiber; (3) Add the dried nano-functional filler and reinforcing fiber and phenolic resin to a high-speed mixer and premix for 10 to 40 minutes at a speed of 500 to 1500 rpm to obtain a premix. (4) The premixed material is plasticized and pulverized to obtain modified phenolic composite material powder; (5) The modified phenolic composite material powder is placed in a rectangular mold and transferred to a flat vulcanizing machine for molding to obtain a modified phenolic composite material board. (6) After heat treatment, the modified phenolic composite material sheet becomes a self-lubricating phenolic resin-based composite material.
[0014] The plasticizing conditions in step (4) are: front roller temperature of 120~150℃, rear roller temperature of 100~120℃, and plasticizing time of 5~25min.
[0015] The crushing conditions in step (4) refer to a rotation speed of 500~1500 rpm and a crushing time of 5~15 min.
[0016] The molding conditions in step (5) are a temperature of 130~190℃, a pressure of 10~35MPa, and a molding time of 5~90min.
[0017] The heat treatment conditions in step (6) refer to heat treatment using a forced-air drying oven at 80~150℃, heating to 200~250℃ at a heating rate of 10~30℃ / min, holding at that temperature for 1~3 hours, and then cooling to room temperature.
[0018] Compared with the prior art, the present invention has the following advantages: 1. This invention optimizes the formulation by adding attapulgite or its derivatives, which act as stress concentration points, and reinforcing fibers. This absorbs applied external energy while preventing the formation and generation of crazes within the material, increasing the flexural and compressive strength of the resin, improving the plastic deformation range of the phenolic resin matrix, and enhancing the toughness of the material.
[0019] 2. This invention introduces attapulgite or its derivatives and reinforcing fibers simultaneously into phenolic resin, exhibiting significant synergistic friction-reducing and wear-resistant effects under both dry and oil lubrication conditions, resulting in extremely low friction coefficients and wear rates. Specifically: In oil lubrication, the silicon and aluminum oxides formed by the frictional oxidation of attapulgite are transferred to the friction mating surface and embedded in the carbon-based friction film formed by the frictional oxidation of reinforcing fibers, promoting the formation of an interfacial hybrid friction film, further enhancing the load-bearing capacity of the friction film, and reducing the friction coefficient and wear rate. Under dry friction, the high thermal conductivity of attapulgite can effectively reduce the high flash temperature in the friction contact area caused by reinforcing fibers, reduce polymer material transfer, thereby reducing the wear rate of the phenolic composite material and improving its service life.
[0020] 3. This invention uses a three-roll calender to plasticize the premixed material, utilizing its efficient shearing to further reduce the particle size inside the material, increase the particle surface area, improve its adhesion to phenolic resin, enhance the dispersion effect of nano-functional fillers and reinforcing fibers in phenolic resin, avoid unevenness caused by poor flowability during molding, and ultimately improve the service life of phenolic composite materials under harsh dry friction and oil lubrication conditions.
[0021] 4. The composite material obtained by this invention is suitable for complex and variable working conditions with harsh dry friction and oil lubrication. As a moving part in high-end equipment fields such as wind power bearings, it can significantly improve the reliability and service life of moving parts, reduce friction energy consumption, and has significant energy-saving and emission-reduction significance. Detailed Implementation
[0022] A self-lubricating phenolic resin-based composite material, comprising the following components in mass fractions (g / g): 55%~85% phenolic resin, 5%~25% nano-functional filler, and 10%~20% reinforcing fiber.
[0023] Among them, phenolic resin is thermosetting phenolic resin powder.
[0024] The nano-functional filler is any one of attapulgite powder or its derivatives, with a particle size of 10 nm to 100 nm. Preferably, the nano-functional filler is attapulgite with a purity greater than 98% and which is dissociated.
[0025] The reinforcing fiber is any one or more mixed fibers selected from carbon fiber, aramid fiber, glass fiber, and titanate whisker fiber, with an aspect ratio greater than 20.
[0026] A method for preparing a self-lubricating phenolic resin-based composite material includes the following steps: (1) Weigh according to the proportions; (2) Dry the nano-functional filler and reinforcing fiber at 60℃~120℃ for 1~24h to obtain the dried nano-functional filler and reinforcing fiber; (3) Add the dried nano-functional filler and reinforcing fiber and phenolic resin to a high-speed mixer and premix for 10 to 40 minutes at a speed of 500 to 1500 rpm to obtain a premix. (4) The premixed material is added to a three-roll calender for plasticizing. The temperature of the front roll is 120~150℃ and the temperature of the rear roll is 100~120℃. The plasticizing time is 5~25min to obtain modified phenolic composite material sheets. The modified phenolic composite material sheets are added to a pulverizer and pulverized at a speed of 500~1500rpm for 5~15min. After plasticizing and pulverizing, modified phenolic composite material powder is obtained. (5) The modified phenolic composite material powder is placed in a rectangular mold and transferred to a flat vulcanizing machine for molding. The temperature is 130~190℃, the pressure is 10~35MPa, and the molding time is 5~90min to obtain the modified phenolic composite material board. ⑹ The modified phenolic composite material board is placed in a forced-air drying oven at 80~150℃ for heat treatment, and the temperature is raised to 200~250℃ at a heating rate of 10~30℃ / min. After holding at the temperature for 1~3h, it is cooled to room temperature to obtain the self-lubricating phenolic resin-based composite material.
[0027] Example 1 A self-lubricating phenolic resin-based composite material, which is composed of the following components: 850g phenolic resin, 50g attapulgite, and 100g carbon fiber.
[0028] Its preparation method includes the following steps: (1) Weigh according to the proportions; (2) The nano-functional filler and reinforcing fiber are dried at 90℃ for 18h to obtain the dried nano-functional filler and reinforcing fiber. (3) Add the dried nano-functional filler and reinforcing fiber and phenolic resin to a high-speed mixer and premix for 30 minutes at a speed of 1000 rpm to obtain a premix. (4) The premixed material is added to a three-roll calender for plasticizing. The front roll temperature is 135℃ and the rear roll temperature is 110℃. The plasticizing is carried out for 15 minutes to obtain modified phenolic composite material sheets. The modified phenolic composite material sheets are added to a pulverizer and pulverized at a speed of 1500 rpm for 5 minutes. After plasticizing and pulverizing, modified phenolic composite material powder is obtained. (5) The modified phenolic composite material powder was placed in a rectangular mold and transferred to a flat vulcanizing machine for molding. The temperature was 180℃, the pressure was 30 MPa, and the molding time was 30 min to obtain the modified phenolic composite material board. ⑹ The modified phenolic composite material board was heat-treated in a forced-air drying oven at 120℃, heated to 240℃ at a heating rate of 20℃ / min, held at that temperature for 2 hours, and then cooled to room temperature to obtain the self-lubricating phenolic resin-based composite material.
[0029] Example 2 A self-lubricating phenolic resin-based composite material, which is composed of the following components: 800g phenolic resin, 100g attapulgite, and 100g carbon fiber.
[0030] The preparation method is the same as in Example 1.
[0031] Example 3 A self-lubricating phenolic resin-based composite material, which is composed of the following components: 700g phenolic resin, 200g attapulgite, and 100g carbon fiber.
[0032] The preparation method is the same as in Example 1.
[0033] Comparative Example 1: A phenolic resin material 1000g of phenolic resin was added to a high-speed mixer and premixed for 30 minutes at 1000rpm. The premix was then quantitatively added to a three-roll calender at a front roll temperature of 135℃ and a rear roll temperature of 110℃, and plasticized for 15 minutes to obtain phenolic material sheets. The sheets were then added to a pulverizer and pulverized for 5 minutes at 1500rpm to obtain phenolic material powder. The obtained powder was placed in a rectangular mold and transferred to a flat vulcanizing machine at a temperature of 180℃ and a pressure of 30 MPa for 30 minutes to obtain phenolic material boards. The obtained boards were then heat-treated in a 120℃ forced-air drying oven, heated to 240℃ at a heating rate of 20℃ / min, held at that temperature for 2 hours, and then cooled to room temperature to obtain solid phenolic material.
[0034] Comparative Example 2: A plastic-free phenolic composite material 50g of attapulgite and 100g of carbon fiber were dried at 90℃ for 18h. The dried nano-functional filler, reinforcing fiber, and 850g of phenolic resin were added to a high-speed mixer and premixed at 1000rpm for 30min. The resulting premixed powder was placed in a rectangular mold and transferred to a flat vulcanizing machine. The mold was pressed at 180℃ and 30MPa for 30min to obtain a modified phenolic composite material board. The obtained board was heat-treated in a 120℃ forced-air drying oven, heated to 240℃ at a heating rate of 20℃ / min, held at that temperature for 2h, and then cooled to room temperature to obtain a solid phenolic composite material.
[0035] Mechanical property testing Mechanical properties of the composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested. Following the standards GB / T 1041-2008 (Determination of Compression Properties of Plastics) and GB / T 9341-2008 (Determination of Flexural Properties of Plastics), the molded sample blocks were machined into shapes of 80×10×4 mm. 3 The compressive and flexural properties of the examples and comparative examples were determined using a universal testing machine. The results of the compressive and flexural strength measurements are shown in Table 1.
[0036] Table 1. Compressive and flexural strengths of materials prepared in the examples and comparative examples As shown in Table 1, the phenolic composite material obtained in this invention exhibits higher compressive and flexural strength compared to pure phenolic resin. This is because attapulgite or its derivatives effectively absorb fracture energy, causing crazes to form within the material. The high-modulus reinforcing fibers inhibit the growth of crazes, improving the plastic deformation range of the phenolic resin matrix and increasing the material's flexural and compressive strength, thus demonstrating higher load-bearing capacity. Simultaneously, the mechanical properties of the phenolic resin composite material are improved after the plasticizing process.
[0037] Tribological property testing Friction tests were conducted on the composite materials obtained in Examples 1-3 and Comparative Examples 1-2 under both dry friction and oil lubrication conditions using a high-speed ring-block testing machine. The molded sample material was machined to a size of 25 × 10 × 4 mm. 3 The mating part is made of GCr15 bearing steel. Both the mating part and the composite material block are polished with sandpaper of the same grit to obtain the same roughness Ra=0.25.
[0038] The dry friction test conditions were: test load 200 N, sliding speed 1 m / s, duration 3 h, with the mating pair exposed to air. The oil lubrication test conditions were: test load 200 N, sliding speed 1 m / s, duration 3 h, with the mating pair immersed in a cavity filled with polyalphaolefin (PAO) oil.
[0039] After the friction experiment, the width of the wear marks was measured using an optical microscope, and the wear rate was calculated using a formula.
[0040] Where L′ is the width of the sample (mm), R is the diameter of the paired steel ring (mm), W is the width of the wear mark (mm), F is the force applied in the normal direction (N), and L is the sliding distance (m).
[0041] The average friction coefficient and wear rate of the obtained materials are shown in Table 2.
[0042] Table 2. Calculation results of average friction coefficient and wear rate of materials prepared in the examples and comparative examples. As can be seen from Table 2, the high-strength wear-resistant phenolic resin composite material (Examples 1-3) obtained by the present invention, which is suitable for harsh dry friction and oil lubrication conditions, has significant friction-reducing and wear-resistant properties compared with pure phenolic resin and phenolic composite materials without plasticizing process (Comparative Examples 1-2). The wear rate is greatly reduced compared with pure resin and composite materials prepared without plasticizing process.
[0043] In dry friction, the high thermal conductivity of attapulgite can effectively reduce the high flash temperature of reinforcing fibers at the friction interface, significantly inhibit the transfer of phenolic resin, and generate a high-strength wear-resistant transfer film through the physical-chemical reaction of interfacial friction, avoiding direct contact between the friction pairs and reducing material wear. In oil-lubricated media, the stress of the reinforcing fibers at the friction interface causes the attapulgite released at the friction interface to be frictionally sintered into a transfer film with high load-bearing capacity and easy shear properties, avoiding direct scraping of the friction pair and greatly reducing the wear rate.
[0044] The above description is merely a specific embodiment of the present invention and does not constitute a limitation on the scope of protection of this patent. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A self-lubricating phenolic resin-based composite material, characterized in that: The composite material is composed of the following components by mass fraction: 55%~85% phenolic resin, 5%~25% nano-functional filler, and 10%~20% reinforcing fiber; wherein the phenolic resin is thermosetting phenolic resin powder; the nano-functional filler is attapulgite powder with a particle size of 10 nm~100 nm; the nano-functional filler is attapulgite with a purity greater than 98% and is dissociated; the preparation method of the composite material includes the following steps: (1) Weigh according to the proportions; (2) Dry the nano-functional filler and reinforcing fiber at 60℃~120℃ for 1~24h to obtain the dried nano-functional filler and reinforcing fiber; (3) Add the dried nano-functional filler and reinforcing fiber and phenolic resin to a high-speed mixer and premix for 10 to 40 minutes at a speed of 500 to 1500 rpm to obtain a premix. (4) The premixed material is plasticized and pulverized using a three-roll calender to obtain modified phenolic composite material powder; (5) The modified phenolic composite material powder is placed in a rectangular mold and transferred to a flat vulcanizing machine for molding to obtain a modified phenolic composite material board. (6) After heat treatment, the modified phenolic composite material sheet becomes a self-lubricating phenolic resin-based composite material.
2. The self-lubricating phenolic resin-based composite material as described in claim 1, characterized in that: The reinforcing fiber is any one or more mixed fibers selected from carbon fiber, aramid fiber, glass fiber, and titanate whisker fiber, with an aspect ratio greater than 20.
3. The self-lubricating phenolic resin-based composite material as described in claim 1, characterized in that: The plasticizing conditions in step (4) are: front roller temperature of 120~150℃, rear roller temperature of 100~120℃, and plasticizing time of 5~25min.
4. The self-lubricating phenolic resin-based composite material as described in claim 1, characterized in that: The crushing conditions in step (4) refer to a rotation speed of 500~1500 rpm and a crushing time of 5~15 min.
5. The self-lubricating phenolic resin-based composite material as described in claim 1, characterized in that: The molding conditions in step (5) are a temperature of 130~190℃, a pressure of 10~35MPa, and a molding time of 5~90min.
6. The self-lubricating phenolic resin-based composite material as described in claim 1, characterized in that: The heat treatment conditions in step (6) refer to heat treatment using a forced-air drying oven at 80~150℃, heating to 200~250℃ at a heating rate of 10~30℃ / min, holding at that temperature for 1~3 hours, and then cooling to room temperature.